Quelle éthique pour les dynamiques inclusives ? Entre préoccupation et humilité - Martine Janner Raimondi (Éducation et Socialisation)
This article raises an ethical question in order to explore the inclusive dynamics that cannot be reduced to a reasoning, even a critical one. Indeed, ethics goes beyond the contents promoted in the fields of practice, theory and politics by questioning them and challenging them because of issues and values that are considered as superior to each of them. It is a form of practical reason more precisely, because it makes it possible to influence the course of life, to steer actions, to exercise powers to act. However, if ethics is by definition perfectionist, the meaning of perfectionism can vary from one conception to another. What ethics does the inclusive paradigm need? This is the problem posed in this paper. First, we will examine the issue from the perspective of a macro analysis of contractualist theories in political philosophy; secondly, the problem will be enlightened through the ethics of care in connection with disability studies; in a third part, we will consider some ethical activities related to the inclusive paradigm, more specifically in the educational field, before broadening some perspectives in conclusion.